-14+6b+7-2b=1+b+5b

Simple and best practice solution for -14+6b+7-2b=1+b+5b equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -14+6b+7-2b=1+b+5b equation:


Simplifying
-14 + 6b + 7 + -2b = 1 + b + 5b

Reorder the terms:
-14 + 7 + 6b + -2b = 1 + b + 5b

Combine like terms: -14 + 7 = -7
-7 + 6b + -2b = 1 + b + 5b

Combine like terms: 6b + -2b = 4b
-7 + 4b = 1 + b + 5b

Combine like terms: b + 5b = 6b
-7 + 4b = 1 + 6b

Solving
-7 + 4b = 1 + 6b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-6b' to each side of the equation.
-7 + 4b + -6b = 1 + 6b + -6b

Combine like terms: 4b + -6b = -2b
-7 + -2b = 1 + 6b + -6b

Combine like terms: 6b + -6b = 0
-7 + -2b = 1 + 0
-7 + -2b = 1

Add '7' to each side of the equation.
-7 + 7 + -2b = 1 + 7

Combine like terms: -7 + 7 = 0
0 + -2b = 1 + 7
-2b = 1 + 7

Combine like terms: 1 + 7 = 8
-2b = 8

Divide each side by '-2'.
b = -4

Simplifying
b = -4

See similar equations:

| x^2+3=x^2+1 | | 12+7-5y=-14 | | 3.00=45b | | 1.8+(2)2.5= | | x^2+hx+10=0 | | -10x^2-x^2= | | 1+c+1.4=c+3.4 | | 7-y= | | (n+4)(n-3)=10 | | 2r+1+(-4r)+7= | | 3x+5y-100=0 | | 1-16x^8=0 | | 10x+3-4x=27 | | x^2+4ax=21a^2 | | x^2-5bx+6b^2=0 | | -25x+14=19 | | 5x+10x=165 | | x^2=cx | | 2x(3-4)+x(5-4)= | | z^2-10z+36=0 | | -3y+8x=-4 | | (x-3)6= | | -3y+8x=-4fory | | -35.73168X=1627 | | 172+p=2000 | | -35.73168=1.96318389 | | 61=4a+b | | 1x+2x-1+2=18 | | 1x+2x-5=17 | | 6x-2=x+11 | | 12x-3=8x-7 | | 2.6t+5.2=2.6t+4+1.2 |

Equations solver categories